Mesoproterozoic intraplate magmatic ‘barcode’ record of the Angola portion of the Congo Craton: Newly dated magmatic events at 1505 and 1110 Ma and implications for Nuna (Columbia) supercontinent reconstructions - Pisarevsky, Sergei; Ernst, R.; Pereira, E.; Hamilton, M.; Rodriques, J.; Tassinari, C.; Teixeira, W.; Van-Dunem, V. (Elsevier BV, 2013)
In the Angola portion of the Congo Craton, the only Proterozoic large igneous province (LIP) dated prior to this study was the 1380–1370 Ma (Kunene Intrusive Complex and related units). U–Pb TIMS ages on baddeleyite from dolerite sills and gabbro-noritic dykes, has revealed two additional Mesoproterozoic intraplate events: at ca. 1505 and ca. 1110 Ma, that are each proposed to be part of the plumbing system for LIPs. The identification of these three Mesoproterozoic magmatic events (ca. 1505, 1380, and 1110 Ma) represent an initial magmatic ‘barcode’ for this portion of Congo Craton (and formerly connected São Francisco Craton), which can be compared with the magmatic ‘barcode’ record of other blocks to identify former nearest neighbors in the Precambrian supercontinent Nuna (also known as Columbia).Specifically, a 1502 ± 5 Ma U–Pb TIMS baddeleyite age has been obtained for the prominent Humpata dolerite sill which is part of a wider sill province in SW Angola portion of the Congo Craton. The combined presence of both 1505 Ma and 1380 Ma magmatism in the Congo–São Francisco reconstructed craton is a match with similar ages published for two intraplate magmatic provinces in northern Siberia and suggests a nearest-neighbor relationship in the supercontinent Nuna in which northern Siberia is juxtaposed adjacent to the western São Francisco portion of the reconstructed São Francisco–Congo Craton.In addition, a precise U–Pb TIMS baddeleyite age of 1110 ± 2.5 Ma was obtained for a prominent NNW–NNE trending gabbro-noritic (GN) dyke swarm in southeastern Angola, but this age is currently unknown in Siberia suggesting that the breakup of Congo–São Francisco Craton from Siberia happened earlier, perhaps in association with the 1380 Ma event. This 1110 Ma age is however, a precise match with that of the Umkondo large igneous province (LIP) of the Kalahari Craton, and also with mafic intraplate magmatism on other blocks such as the Bundelkhand Craton (India) and the Amazonian Craton. We provisionally consider these three cratons to have been nearest neighbors to the Congo–São Francisco Craton at this time and to have shared this 1110 Ma magmatic event as a LIP node. There is also an age match with the early part of the Keweenawan event (in the interior of the Laurentia); however, on previously discussed paleomagnetic grounds the Keweenawan event is likely to have been distant and unrelated (and on the other side of the Grenville orogen).